HUBUNGAN FAKTOR PERILAKU DENGAN KELENGKAPAN PENGISIAN DATA KMS DALAM BUKU KIA OLEH KADER POSYANDU DI WILAYAH KERJA PUSKESMAS SIDOREJO LOR SALATIGA TAHUN 2016 - Catur Putri Ariyanti; Yudhy Dharmawan; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2016)
The prevalence of malnourished children in Indonesia tends to increase. One of the efforts used to prevent this malnutrition is by monitoring the growth of infants in the Posyandu by used the Growth Chart in Maternal and Child Health (MCH) Handbook. The data of Growth Chart is recorded by the Community Health Volunteer (CHV). It is important to record the data of growth Chart for infants, and the health workers as the source information in decision-making and precautionary measures. The preliminary results of the observations of 20 Growth Chart in Puskesmas Sidorejo Lor Salatiga, is still lackingin the matter of completeness. The objective of this study is to analyze the correlationof the behavioral factors to the completeness of Growth Chart in MCH Handbook in Puskesmas Sidorejo Lor Salatiga. This type of research is Explanatory Research with Cross Sectional study design. The population in this study is 447 CHVs and sample are taken by using convinence sampling and it is found that there are 63 CHVs with criteria CHVs who record the Growth Chart when the Posyandu is open. Univariate and bivariate analysis are applied in the data analysis. The result of the study showed that the largest percentage of aged CHVs were in the age group of 45-49 years (27.0%), with the high school education (55.6%), have become cadre for 6-20 years (23.8%), the number of infants served are 21-30 infants (25.4%), insufficient knowledge (76.2%), with sufficient motivation (55.6%), and the less completeness of KMS (87.3%). The result of Spearman Rank analysis (α=5%) shows that there is significant correlate between how long they have become CHV and the completeness of the Growth Chart in MCH Handbook (p value = 0.047; rs = 0.251; 95% CI = -0,052-0,405). There are no correlation between age (p value = 0,900), education (p value = 0.888), the number of infants (p value = 0.505), knowledge (p value = 0.873), and motivation (p value = 0.188) with the completeness of Growth Chart in MCH Handbook. It is suggested for Puskesmas Sidorejo Lor to optimize the refreshing program of CHV, in order to avoid drop out CHV.